2023
DOI: 10.3389/fphar.2023.1096159
|View full text |Cite
|
Sign up to set email alerts
|

Multiomics integration reveals the effect of Orexin A on glioblastoma

Abstract: Objectives: This study involved a multi-omics analysis of glioblastoma (GBM) samples to elaborate the potential mechanism of drug treatment.Methods: The GBM cells treated with or without orexin A were acquired from sequencing analysis. Differentially expressed genes/proteins/metabolites (DEGs/ DEPs/ DEMs) were screened. Next, combination analyses were conducted to investigate the common pathways and correlations between the two groups. Lastly, transcriptome-proteome-metabolome association analysis was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…A total of 1572 DEGs, 52 DEPs and 116 DEMs were identified in our previous studies (Figure 2A–D ). 22 The result of KEGG enrichment analysis for transcriptome‐proteome‐metabolome combination showed that 11 common pathways were significantly enriched by DEGs, DEPs and DEMs, and ferroptosis is one of them. (Figure 2E ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 1572 DEGs, 52 DEPs and 116 DEMs were identified in our previous studies (Figure 2A–D ). 22 The result of KEGG enrichment analysis for transcriptome‐proteome‐metabolome combination showed that 11 common pathways were significantly enriched by DEGs, DEPs and DEMs, and ferroptosis is one of them. (Figure 2E ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, our previous investigations have revealed the antitumor role of orexin‐A in GBM. Through multiple histological analyses of the transcriptome, proteome and metabolome, we have observed that orexin‐A may potentially target ferroptosis, although the specific mechanism remains unclear 22,23 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among this large family of GPCRs, the orexins/OX receptor system, which has been extensively studied for its effects on the central nervous system [28], has recently been shown to have anti-inflammatory and anti-tumor properties at the peripheral level [11,14]. In fact, orexins have been demonstrated to induce an antitumor effect against digestive cancers such as colon cancer, pancreatic cancer, and liver cancer as well as nondigestive cancers including prostate cancer [19], and more recently glioblastoma [21]. This breakthrough paradigm revealed that the orexins/OX receptors system could represent a new innovative target in cancer therapy [29].…”
Section: Discussionmentioning
confidence: 99%
“…In digestive cancer cells, OX1R activation by orexins induced a mitochondrial apoptosis mediated by the recruitment of the tyrosine phosphatase SHP2 [11]. This pro‐apoptotic properties of orexins in cancer cells were induced in a preclinical mouse model where cancer cells from colon or pancreas tumor cells were subcutaneously xenografted in mice, causing strong tumor regression [17, 20, 21]. These observations indicated that the orexins/OX1R system could represent a putative target in the treatment of digestive cancers [11].…”
Section: Introductionmentioning
confidence: 99%